Does exposure to asbestos cause prostate cancer? A systematic literature review and meta-analysis. Issue 3 (January 2019) - Peng, Rui; Fang, Fang; Chen, Zhijun; Yang, Shuai; Dai, Changyuan; Wang, Chengyong; Guan, Han; Li, Qingwen
Abstract: Objective: The relationship between asbestos and prostate cancer (PCa) is not well understood due to small number of cases. This study aimed to determine the incidence and mortality of PCa among workers or residents exposed to asbestos based on a systematic review and meta-analysis Methods: All published studies citing the standardized mortality ratio (SMR) or standardized incidence ratio (SIR) of PCa in workers or residents exposed to asbestos were collected by conducting a search on PubMed, EMBASE, Cochrane Library, and Web of Science before April 2018. Standardized mortality rate for PCa with its 95% confidence interval (CI) was pooled using a fixed-/random-effect model in STATA (Version14.0). This study is registered with PROSPERO, number CRD42018095195. Results: A total of 17 independent studies were included for the analysis. The overall pooled SMR of PCa was 1.22, with a 95% CI of 1.13 to 1.32, with no heterogeneity across the studies (I 2  = 18.8%, P  = .234). Subgroup analysis shows that exposure to crocidolite, cement, studies conducted in Europe and Oceania, and long study follow-up (≥25 years) all contribute to significantly higher SMR, and we found no evidence of publication bias (Begg test P value = .592, Egger test P value = .874). Conclusions: This meta-analysis suggested that exposed to asbestos might be associated with an increased risk of PCa. High-exposure level of asbestos could contribute to significantly higher risk of PCa mortality. Abstract : Supplemental Digital Content is available in the text